Chemical composition and thermal properties of commercial essential oils and their antimicrobial and antioxidant activities (Research, Society and Development, 2023)
This study aimed to chemically characterize commercial Essentials oils and determine their thermal properties and their antimicrobial and antioxidant activities. Essential oils extracted from leaves of Rosemary, lemongrass, cloves, orange, Tahiti lemon and thyme were studied, with chemical characterization by gas chromatography/mass spectrometry, thermoanalytical characterization and antimicrobial (microdilution) and antioxidant (ferric reduction activities power - FRAP). The chemistry of the essential oils composition was consistent with literature data and justified their thermal behavior. Comparing the thermal stability between the studied essential oils results revealed the optimization of the da Tonset = 106.6to clove`s essential oils. The results of differentiated antimicrobial and antioxidant activity justified by factors that influence the biological functions of Essentials oils, such as the origin of the plant (climate conditions), forms of cultivation and harvesting of the raw material, parameters and extraction method. Thus, it emphasizes the importance of a Brazilian production of essentials to take advantage of the technological and analytical capacity of national research centers, to provide the market with traceable products with certified identity.